Nasopharyngeal carriage of Streptococcus pneumoniae among Brazilian children: Interplay with viral co-infection - Kauana Pizzutti; Juliana Comerlato; Daniele Vargas de Oliveira; Amanda Robaina; Mariana Preussler Mott; Pedro Uriel Pedrotti Vieira; Tiago Fetzner; Gabriela Rosa da Cunha; Muriel Primon de Barros; Jaqueline Verardo; Neide Maria Bruscato; João Carlos Batista Santana; et al. (PLoS ONE, 2025)
Nasopharyngeal transmission of Streptococcus pneumoniae is a prerequisite for the development of pneumococcal diseases. Previous studies have reported a relationship between respiratory viruses and S. pneumoniae infections. However, there are few studies on this issue among healthy children. This study aimed to examine the relationships between these agents in healthy children from Southern Brazil. This cohort study included 229 nasopharyngeal samples collected from children aged 18–59 months at baseline. S. pneumoniae was detected using bacterial culture, whereas respiratory viruses were identified using quantitative polymerase chain reaction. A questionnaire was used at the time of sample collection and medical records were reviewed 14 days after participant inclusion. The prevalence of pneumococcal carriage was 63.7% (146/229), while respiratory viruses were detected in 49.3% (113/229) of the children. Respiratory viruses were more frequently found among pneumococcal carriers than among non-carriers (54.4% vs. 39.7%, p = 0.033). Additionally, rhinovirus (hRV) was more frequent among the pneumococcal carriers (39% vs. 21.7%, p = 0.012), and the presence of human bocavirus (hBOV) alone was associated with the absence of pneumococcal carriage (2.7% vs. 10.8%, p = 0.016). No differences were found in the frequency of pneumococcal carriage, respiratory virus detection, or the co-occurrence of clinical symptoms and diagnosis in the participants 14 days after specimen collection. Our findings revealed a positive relationship between pneumococcal carriage and respiratory virus detection, particularly for hRV. However, we did not observe a relationship between nasopharyngeal respiratory viruses and pneumococci detection during medical appointments, respiratory symptoms, or diseases. This study was one of the first investigations in Latin America to explore the relationship between respiratory viruses and pneumococcal carriage in a healthy children.